STUDY AND IMPROVEMENT OF PERFORMANCE OF NoSQL DATABASES: MongoDB, HBase and OrientDB. - Noel Bila; Bopatriciat Boluma Mangata; Eugène MBUYI MUKENDI; Parfum BUKANGA CHRISTIAN (STMIK Pringsewu Lampung, 2022)
This dissertation adds to the various research works in the field of NoSQL